Antibiotic Overuse in Children with Respiratory Syncytial Virus Lower Respiratory Tract Infection. Issue 11 (November 2018) - van Houten, Chantal B.; Naaktgeboren, Christiana; Buiteman, Brigitte J. M.; van der Lee, Maaike; Klein, Adi; Srugo, Isaac; Chistyakov, Irena; de Waal, Wouter; Meijssen, Clemens B.; Meijers, Pieter W.; de Winter-de Groot, Karin M.; Wolfs, Tom F.W.; et al.
Abstract : Background: Respiratory syncytial virus (RSV) is the most common cause of lower respiratory tract infections (LRTI) during the first year of life. Antibiotic treatment is recommended in cases suspected of bacterial coinfection. The aim of this prospective study was to estimate the incidence of bacterial coinfections and the amount of antibiotic overuse in children infected with RSV using expert panel diagnosis. Methods: Children 1 month of age and over with LRTI or fever without source were prospectively recruited in hospitals in the Netherlands and Israel. Children with confirmed RSV infection by Polymerase Chain Reaction (PCR) on nasal swabs were evaluated by an expert panel as reference standard diagnosis. Three experienced pediatricians distinguished bacterial coinfection from simple viral infection using all available clinical information, including all microbiologic evaluations and a 28-day follow-up evaluation. Results: A total of 188 children (24% of all 784 recruited patients) were positive for RSV. From these, 92 (49%) were treated with antibiotics. All 27 children (29%) with bacterial coinfection were treated with antibiotics. Fifty-seven patients (62%) were treated with antibiotics without a diagnosis of bacterial coinfection. In 8 of the 92 (9%), the expert panel could not distinguish simple viral infection from bacterial coinfection. Conclusion: This is the first prospective international multicenter RSV study using an expert panel as reference standard to identify children with and without bacterial coinfection. All cases of bacterial coinfections are treated, whereas as many as one-third of all children with RSV LRTI are treated unnecessarily with antibiotics.